Prevalence of Metabolic Syndrome in Women With Polycystic Ovarian Diseases in a Outdoor Setting - Chowdhury, Shahanara; Ferdous , Afroza (Journal of Chittagong Medical College Teachers' Association, 2013)
Polycystic ovarian diseases (PCOD) is a condition associated with chronic anovulation, insulin resistance and androgen access. Women with this syndrome are at increased risk of metabolic syndrome. The aim of the present study was to determine the prevalence of metabolic syndrome (MBS) in women with PCOD in a private outdoor setting in different ages and body mass index (BMI). A cross sectional study was conducted in a private clinic setting. A total of 146 women with PCOD ages between 15-40 years included. The prevalence of metabolic syndrome and its components in these population were the outcomes. Height, weight, waist circumference, blood pressure and the laboratory tests (FBS,TSH,HDLC, serum prolactin, triglycerides and total cholesterol) were measured in this population. The prevalence of MBS in PCOD women was 24% (36 cases). The rate of central obesity, FBS more than 110 mg/dl, triglycerides more than 150 mg/dl, high-density lipoprotein cholesterol levels (HDL-C) less than 50 mg/dl, and blood pressure 130/85 mmHg in PCOD women was 29.45% (43), 4.10% (6), 34.93% (51), 66.43% (97), and 10.27% (15), respectively. The risk of MBS was increased in older and the obese women (BMI 30 kg/m2). The present study showed that women with PCOD have high prevalence of MBS & its individual components, particularly decreased HDL-C. JCMCTA 2012 ; 23 (2): 18-21